2004
DOI: 10.1093/ije/dyh155
|View full text |Cite
|
Sign up to set email alerts
|

Does conflict between home and work explain the effect of multiple roles on mental health? A comparative study of Finland, Japan, and the UK

Abstract: Both work-to-family and family-to-work conflict affect the mental health of men and women in three different countries. Work and family roles and the balance between the two may be important for the mental health of men and women in industrialized societies. Any analysis of the effect of multiple roles on health needs to take into account the psychosocial content of such roles.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
138
2
5

Year Published

2005
2005
2015
2015

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 165 publications
(154 citation statements)
references
References 19 publications
9
138
2
5
Order By: Relevance
“…Accordingly, previous studies have suggested that paid work represents an additional workload in particular for women (Bartley et al, 1992). However, current evidence suggests that the overall prevalence and level of work to family and family to work conflicts are relatively similar among women and men (Chandola et al, 2004;Kinnunen & Mauno, 1998). Also results of a meta-analysis showed that levels of family to work and work to family conflicts are similar among women and men suggesting that gender is unlikely an antecedent of work-family conflicts (Byron, 2005).…”
Section: Theoretical Framework For the Study Of Work Family Interfacementioning
confidence: 96%
“…Accordingly, previous studies have suggested that paid work represents an additional workload in particular for women (Bartley et al, 1992). However, current evidence suggests that the overall prevalence and level of work to family and family to work conflicts are relatively similar among women and men (Chandola et al, 2004;Kinnunen & Mauno, 1998). Also results of a meta-analysis showed that levels of family to work and work to family conflicts are similar among women and men suggesting that gender is unlikely an antecedent of work-family conflicts (Byron, 2005).…”
Section: Theoretical Framework For the Study Of Work Family Interfacementioning
confidence: 96%
“…20 Furthermore, work-related factors might be modified by the simultaneous demands of family roles, a phenomenon known as the work-home interface, and this has been shown to be associated with health and well-being. [21][22][23][24] However, the effects of the work-home interface on weight gain have not been studied. To control the weight gain epidemic, more information on work-related factors underlying weight gain is needed.…”
Section: Introductionmentioning
confidence: 99%
“…"Workfamily conflict" (WFC) can arise when "efforts to fulfill the demands of the employee role interfere with the ability to fulfill the demands of the roles as a spouse, parent, or carer" (7). Another similar term commonly used is "work-home interference" (WHI) (8) although this does not necessarily refer to impact on the role as a spouse, parent, or carer.…”
mentioning
confidence: 99%